Adaptation of supply management towards a hybrid culture: the case of a Japanese automaker. Issue 1 (11th January 2016) - Jia, Fu; Gao, Ruihong; Lamming, Richard; Wilding, Richard
Abstract : Purpose: – This paper aims to identify problems caused by cultural differences between Japan and China that face supply chain managers by applying Japanese-style supply management practices within supply networks in China and present solutions to this problem. Design/methodology/approach: – A single, longitudinal case study conducting two waves of data collection (i.e. interviews and observation) plus the collection of much archival data was performed. It goes beyond the dyad by examining supply management of a Japanese company's supply chain up to three tiers in China. Findings: – The four supply cultural differences between Japan and China, which caused the cultural clashes between JVCo and some of its suppliers were revealed and a model of adaptation of Japanese supply management to the Chinese business system was developed. Adaptation involves creating new supply management practices out of selective adaptation, innovation and change of existing Japanese and Chinese supply management practices rooted in different Japanese, Chinese and Western cultures. A list of organisational factors affecting the adaptation has also been provided. Research limitations/implications: – Due to the adoption of a single case study method, caution should be given to generalising the findings to all Japanese firms. Practical implications: – The Japanese, Chinese and Western managers were provided with insights on how to mitigate the problems caused by cultural differences within supply relationships in China and some innovative ideas on how managers from all three cultures could blend the elements of the three cultures to form a hybrid culture and reduce cultural clashes. Originality/value: – This is one of the few attempts to study the transfer of Japanese supply management practice to China. Organizational theory (i.e. transfer of organizational practice and hybridization) is applied and provides a robust framework to explain the supply management practice. This study also answers the call for a global supplier relationship management paradigm.